Comparison of custom-designed oral stents in radiotherapy for head and neck malignancies - Li, Shihang; Pang, Guobao; Li, Rong; Shi, Qinying; Xu, Yannan; Lu, Ying; Song, Jianbo (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeTo compare the 3D-printed oral stents (3D-OS) and personalised hand-made stents in dentistry (DentStent) for head and neck malignancies.MethodsTwelve patients with head and neck malignant tumours in the Cancer Centre of Shanxi Bethune Hospital from 1 August 2023 to 31 September 2024 were admitted to the study. After obtaining informed consent from the patients, 3D-OS and DentStent were designed for each patient, respectively, and the patients wore them to produce two groups of radiotherapy plans. The aim was to compare the homogeneity index (HI) and conformity index (CI) of the target areas, as well as the dose differences to the organs at risk (OAR) between the two plans. Additionally, the satisfaction of the patients with the stents after use was assessed.ResultsThe difference in HI, CI and OAR dose to the target area between the two groups was slight, but 3D-OS took less time (∼4 h) to fabricate and resulted in higher resolution and patient satisfaction.ConclusionThe proposed 3D-OS could obtain good HI and CI in radiotherapy for head and neck malignancies, and is a new method for rapid and satisfactory personalised oral stent.